2014
DOI: 10.1002/anie.201403980
|View full text |Cite
|
Sign up to set email alerts
|

Selective Capture of Carbon Dioxide under Humid Conditions by Hydrophobic Chabazite‐Type Zeolitic Imidazolate Frameworks

Abstract: Hydrophobic zeolitic imidazolate frameworks (ZIFs) with the chabazite (CHA) topology are synthesized by incorporating two distinct imidazolate links. Zn(2-mIm)0.86 (bbIm)1.14 (ZIF-300), Zn(2-mIm)0.94 (cbIm)1.06 (ZIF-301), and Zn(2-mIm)0.67 (mbIm)1.33 (ZIF-302), where 2-mIm = 2-methylimidazolate, bbIm = 5(6)-bromobenzimidazolate, cbIm = 5(6)-chlorobenzimidazolate, and mbIm = 5(6)-methylbenzimidazolate, were prepared by reacting zinc nitrate tetrahydrate and 2-mIm with the respective bIm link in a mixture of N,N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
135
1
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 242 publications
(148 citation statements)
references
References 33 publications
9
135
1
3
Order By: Relevance
“…Nevertheless, some reports have also emerged describing the selective adsorption of CO 2 over other gases (i.e., N 2 , CH 4 , O 2 , C 2 H 2 or CO), some of which even comprise binary (e.g., CO 2 /CO, CO 2 /N 2 or CO 2 /CH 4 ) and ternary (CO 2 /N 2 /CH 4 , CO 2 /N 2 /H 2 O or CO 2 /N 2 /O 2 ) gas mixtures. 116,117,[125][126][127][128][129][130][131][132] Wang et al reported two porous zeolite-type imidazolate frameworks, coined as ZIF-95 and ZIF-100, possessing complex cages with 264 vertices and constructed from about 7524 atoms. 125 After breakthrough experiments it was discovered that these ZIFs have a great ability to selective adsorb CO 2 from mixtures of CO 2 /CH 4 , CO 2 /CO and CO 2 /N 2 (50:50 v/v).…”
Section: -Co 2 Capturementioning
confidence: 99%
“…Nevertheless, some reports have also emerged describing the selective adsorption of CO 2 over other gases (i.e., N 2 , CH 4 , O 2 , C 2 H 2 or CO), some of which even comprise binary (e.g., CO 2 /CO, CO 2 /N 2 or CO 2 /CH 4 ) and ternary (CO 2 /N 2 /CH 4 , CO 2 /N 2 /H 2 O or CO 2 /N 2 /O 2 ) gas mixtures. 116,117,[125][126][127][128][129][130][131][132] Wang et al reported two porous zeolite-type imidazolate frameworks, coined as ZIF-95 and ZIF-100, possessing complex cages with 264 vertices and constructed from about 7524 atoms. 125 After breakthrough experiments it was discovered that these ZIFs have a great ability to selective adsorb CO 2 from mixtures of CO 2 /CH 4 , CO 2 /CO and CO 2 /N 2 (50:50 v/v).…”
Section: -Co 2 Capturementioning
confidence: 99%
“…(MOFs), 14,15 zeolitic imidazolate frameworks (ZIFs) 16,17 and porous polymer networks (PPNs). 18,19 In the current work, we focus on zeolites.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies pointed out the presence of CO 2 and water inside these porous materials [7,8]. Due to propitious structural properties and electronic distributions at the microscopic level, industrial complications are encountered because of the competition between water and CO 2 during the separation or storage processes.…”
Section: Introductionmentioning
confidence: 99%